Organoleptic Quality of Corn Flour (Zea mays l.) by Oven Method - Abriana, Andi; Tenri Fitriyah, Andi; Laga, Suriana; Sumiati, Sumiati (Hasanuddin University Food Science and Technology Study Program, 2020)
Diversification of processed corn into flour increases corn value. Corn flour is a fine grain from dried corn. This study was carried out to determine the organoleptic quality of corn flour (texture, color, and aroma) through the drying process by the oven method. The best moisture test of dried corn flour was at 80°C, with 7.5% of moisture content, and 3 hours of the drying process. The organoleptic test showed a different score of aroma, color, and texture at various temperatures. Based on panelist assessments showed that 3.71 of aroma score (rather like), 3.86 of color score (rather like), and 2.86 of texture (like moderately) at 60°C; 3.71 of aroma, color, and texture score (like) at 70°C; 4.14 of aroma score (like), 3.71 of color score (rather like), and 4.86 of texture score (like very much) at 80°C. The best result from organoleptic evaluation test was corn flour by drying at 80 ° C with 4.24 of average score and included preferred category.